Quantificação de perda de solos em bacia hidrográfica de primeira ordem : córrego Zaúna, Maringá-PR - Uema, Diogo Yukio (2018)
Laminar erosion is the object of study in several scientific researches, worldwide, nowadays. The present dissertation has the objective of applying different methodological procedures that quantify the laminar erosion, among them the Universal Soil Loss Equation (EUPS), calculated with the Gisus-m addendum of Arcgis, which quantifies soil losses (RPS), also known as the sediment input ratio (RAS), which in turn quantifies the sediments that have been transported to the watershed exudation. Subtracting the data from the EUPS and RPS, it was possible to identify the amount of sediment retained within the Zauna stream water catchment area, located in the municipality of Maringá-Paraná, generating a general diagnosis of the amount of soil loss produced, transported and retained in the studied river basin. In addition, analyzes of soil porosity and hydrosediments were carried out to compare the simulated data (EUPS and RPS) with the actual soil and water data. The study period was from July 2016 to June 2017. The results showed areas with low soil loss values in the watershed, with a higher incidence of soil losses between 0-3 and 3-5 (ton / ha ) spatially distributed throughout the river basin. The different RPS / RAS methodologies presented similar results, with an average of 0.32%, with a greater reality of Vanoni's proposal (1975), resulting in 0.27% and the method with greater distinction of results, extrapolating the results of the EUPS , was that of Willians & Berndt (1977), presenting 16.23%. The porosity of the soil was uniform with normal soil conditions, microporosity around 50%, macroporosity 10% and total porosity 52%. Most of the hydrosediments presented below-expected values in comparison with the maximum quantity established by CONAMA 357/2005 and data from small streams surveys, ranging from 0.0056 to 0.0468 mg / L for suspended solids, 0.0268 to 0.0116 mg / L for dissolved solids and between 0.0736 and 0.12216 mg / L for total solids. The combination of methodologies, in order to elaborate a general diagnosis, presents an improvement in the results and in the study of the dynamics in watersheds. The study scale helped to compare and detail these analyzes